Dosimetric evaluation of synthetic CT relative to bulk density assignment-based magnetic resonance-only approaches for prostate radiotherapy - Kim, Joshua (Radiat Oncol, 2015)
BACKGROUND: Magnetic resonance imaging (MRI) has been incorporated as an adjunct to CT to take advantage of its excellent soft tissue contrast for contouring. MR-only treatment planning approaches have been developed to avoid errors introduced during the MR-CT registration process. The purpose of this study is to evaluate calculated dose distributions after incorporating a novel synthetic CT (synCT) derived from magnetic resonance simulation images into prostate cancer treatment planning and to compare dose distributions calculated using three previously published MR-only treatment planning methodologies. METHODS: An IRB-approved retrospective study evaluated 15 prostate cancer patients that underwent IMRT (n = 11) or arc therapy (n = 4) to a total dose of 70.2-79.2 Gy. Original treatment plans were derived from CT simulation images (CT-SIM). T1-weighted, T2-weighted, and balanced turbo field echo images were acquired on a 1.0 T high field open MR simulator with patients immobilized in treatment position. Four MR-derived images were studied: bulk density assignment (10 HU) to water (MR(W)), bulk density assignments to water and bone with pelvic bone values derived either from literature (491 HU, MR(W+B491)) or from CT-SIM population average bone values (300 HU, MR(W+B300)), and synCTs. Plans were recalculated using fixed monitor units, plan dosimetry was evaluated, and local dose differences were characterized using gamma analysis (1 %/1 mm dose difference/distance to agreement). RESULTS: While synCT provided closest agreement to CT-SIM for D95, D99, and mean dose (<0.7 Gy (1 %)) compared to MR(W,) MR(W+B491), and MR(W+B300), pairwise comparisons showed differences were not significant (p < 0.05). Significant improvements were observed for synCT in the bladder, but not for rectum or penile bulb. SynCT gamma analysis pass rates (97.2 %) evaluated at 1 %/1 mm exceeded those from MR(W) (94.7 %), MR(W+B300) (94.0 %), or MR(W+B491) (90.4 %). One subject’s synCT gamma (1 %/1 mm) results (89.9 %) were lower than MR(W) (98.7 %) and MR(W+B300) (96.7 %) due to increased rectal gas during MR-simulation that did not affect bulk density assignment-based calculations but was reflected in higher rectal doses for synCT. CONCLUSIONS: SynCT values provided closest dosimetric and gamma analysis agreement to CT-SIM compared to bulk density assignment-based CT surrogates. SynCTs may provide additional clinical value in treatment sites with greater air-to-soft tissue ratio.